Evaluation of Irrigation Water Availability and Demand in Blang Rongka, Bener Meriah District - Cut Azizah; Aulia Rahmat; Mirza Fahmi (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2023)
Evaluating the availability of irrigation water is a paramount phase in planning and managing an irrigation network system. This research aimed to calculate the availability and demand of irrigation water in the area of Blang Rongka, Timang Gajah Subdistrict, Bener Meriah District. Blang Rongka irrigation waters 81 hectares of rice fields from the Peusangan watershed. There are 408 households in Blang Rongka Village, with an estimated population of 1.418 people, consisting of 743 men and 675 women, with 43% of the population working as farmers. The data used in this research were primary and secondary. Preliminary data includes flow velocity, channel dimension, and a set of questionnaires. Secondary data includes irrigation network schemes, topography, demographics, and climate data. In addition, we also measure water discharge using the buoy method (manual) by finding the cross-sectional area and flow velocity. This research showed that the average value of water availability is compatible with the cropping pattern (paddy – palawija – paddy). The level of farmers’ satisfaction with irrigation was 80% while the level of water adequacy was 85%. The results have proven that the current irrigation is highly beneficial for farmers.